Aplicación del análisis de redes al estudio de la investigación española de historia de la ciencia. - Osca-Lluch, Julia (REDES: Revista Hispana para el Análisis de Redes Sociales, 2010)
This paper analyzes the patterns of cooperation in Spain researchers in history of science, through an analysis of co-authorship in scientific publications in the area, contained in the databases Social Science Citation Index (SSCI) and Science Citation Index (SCI) for the period 1990-2009. The results show an increase in scientific output over a limited period and scientific collaboration, as only 18,61% of the papers have been signed by more than one author.